Jogjaprov.go.id Website Management in Realizing Good Governance of the Special Government of Yogyakarta Period 2019 - Aisyah, Alfiyani (Universitas Muhammadiyah Yogyakarta, 2022)
Disclosure of information becomes an important part of governance to create good governance or good governance. One of the efforts of the DIY regional government to realize good governance is through transparent information disclosure. The website jogjaprov.go.id managed by the public relations government of DIY never got the most innovative service website in the year 2019 and the first ranking award of Best smart Governance. Public relations of DIY regional government use the website as one of the information media to implement e-government so that people can access and know the information quickly. As for the management of the website, the public relations of DIY regional Government conducted several stages as follows: searching and collecting content, editing, verification and publication on the website jogjaprov.go.id. Content on the jogjaprov.go.id also has several categories, including infrastructure, economics, society, culture, health, education and tourism. This research aimed to analyze the management of jogjaprov.go.id website in realizing the governance of the special region of Yogyakarta in 2019. The research methods in this study were qualitative descriptive with the collection of data through interviews, observations and documentation. The data validity test was through data triangulation. The results showed that the management of the website underwent a change of task from earlier that manages the Department of DIY Communication and informatics, then now moved to public relations of DIY regional government. It can be noted that the public relations of the DIY regional government have been utilizing the website as an information disclosure media to achieve good governance with one aspect of transparency, but the monitoring and evaluation of website content have not been running quite well. As for the website management of public relations of DIY regional government is done through searching and collecting content, editing, verifying, and publishing on jogjaprov.go.id.